(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Paraquat (PQ) is a highly toxic herbicide which causes cellular damage by production of superoxide radicals or other reactive oxygen species (ROS) and nitrite radicals. Agricultural health hazards of PQ are seen among the handlers due to its direct effect. However, most fatal toxicity is seen following ingestion; which is mostly done for self-harm. The target organ of PQ toxicity is lungs and kidney causing very rapid death following extensive pulmonary fibrosis and kidney damage. It also causes local effect on oral cavity by extensive erosion of oral mucosa and tongue. There is no specific treatment due to lack of antidot. In our study, we have seen 57 cases of PQ poisoning brought to our tertiary care centre in southern part of India. Out of these cases, 21 patients were brought directly by family members and remaining were referred from outside. All of the patients received conservative treatment and there was good clinical outcome with 15 deaths. Autopsy was conducted in all deaths in our mortuary. The autopsy findings also highlighted extensive pulmonary damage in all cases.